2022
DOI: 10.1002/ps.7215
|View full text |Cite
|
Sign up to set email alerts
|

Seed treatment with chlorantraniliprole and carbaryl mixture for managing fall armyworm on maize: systemic synergism, control efficiency and synergistic mechanism

Abstract: BACKGROUND: Fall armyworm (Spodoptera frugiperda) is one of the major invasive pests in China, and has been widely controlled by labor-intensive foliar sprays of agrochemicals in maize (Zea mays L.). RESULTS: Systemic bioassay showed that mixtures of chlorantraniliprole (Chlor) and carbaryl (Carb) had dramatically synergistic effect on toxicity to S. frugiperda. Particularly, a mixture of Chlor with Carb at a mass ratio of 2:1 (MCC) exhibited the highest toxicity to S. frugiperda. Therefore, seed treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In line with our results, several studies have highlighted the efficacy of Chlorantraniliprole and Spinetoram in controlling FA infestation. For instance, a study by Wang et al (2023) demonstrated that Chlorantraniliprole effectively reduced FA populations in maize fields. Similarly, Spinetoram has shown promising results in reducing FA damage in the study conducted by Deshmukh et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, several studies have highlighted the efficacy of Chlorantraniliprole and Spinetoram in controlling FA infestation. For instance, a study by Wang et al (2023) demonstrated that Chlorantraniliprole effectively reduced FA populations in maize fields. Similarly, Spinetoram has shown promising results in reducing FA damage in the study conducted by Deshmukh et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…One of the major challenges to ensuring food security for global consumers in the world is the development of rapid detection techniques for detecting pesticide residues and their metabolites in foodstuffs. , Their bioaccumulation in agricultural land that is highly dangerous for human health may be derived from unregulated and excessive usage and thus adversely impact the quality and safety of foodstuffs. , Therefore, developing a robust analytical method for detecting residual pesticides in foodstuffs and monitoring their concentration in the environment is necessary. Among those residual pesticides commonly found in foodstuffs, carbaryl as a carbamate family has been widely used to increase production in agricultural lands due to its high efficiency and powerful activity in controlling the population of harmful insects to a variety of plant crops. , When the carbaryl residue occurs in food and subsequently enters the human body, it can cause a great threat and lead to several serious failures and hazards in the metabolic system. Moreover, the European Union (EU) has regulated the maximum residue limits (MRLs) of carbaryl concentration in several foodstuffs from 0.01 to 0.05 mg kg –1 . Meanwhile, the United States Environmental Protection Agency (US EPA) has established the MRLs for cabbage, leafy, and root vegetables at 21, 10, and 75 mg kg –1 , respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Among those residual pesticides commonly found in foodstuffs, carbaryl as a carbamate family has been widely used to increase production in agricultural lands due to its high efficiency and powerful activity in controlling the population of harmful insects to a variety of plant crops. 5 , 6 When the carbaryl residue occurs in food and subsequently enters the human body, it can cause a great threat and lead to several serious failures and hazards in the metabolic system. 7 9 Moreover, the European Union (EU) has regulated the maximum residue limits (MRLs) of carbaryl concentration in several foodstuffs from 0.01 to 0.05 mg kg –1 .…”
Section: Introductionmentioning
confidence: 99%